2021
DOI: 10.3390/molecules26216511
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Structure Determination, Antioxidant Voltammetry Studies of Butein and 2′,4′-Dihydroxy-3,4-dimethoxychalcone. Computational Studies of 4 Structurally Related 2′,4′-diOH Chalcones to Examine Their Antimalarial Activity by Binding to Falcipain-2

Abstract: Malaria is a huge global health burden with resistance to currently available medicines resulting in the search for newer antimalarial compounds from traditional medicinal plants in malaria-endemic regions. Previous studies on two chalcones, homobutein and 5-prenylbutein, present in E. abyssinica, have shown moderate antiplasmodial activity. Here, we describe results from experimental and computational investigations of four structurally related chalcones, butein, 2′,4′-dihydroxy-3,4-dimethoxychalcone (DHDM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
(68 reference statements)
1
7
0
Order By: Relevance
“…Shorter single bonds and longer double bonds can be associated with ring aromatization, suggesting the unpaired electron of superoxide is donated to the quinone ring. This result has already been observed by us in related polyphenols scavenging superoxide [ 21 ]. The electron captured by the ring also has an effect on the C=O bond lengths as they become elongated by 0.03 Å.…”
Section: Resultssupporting
confidence: 84%
“…Shorter single bonds and longer double bonds can be associated with ring aromatization, suggesting the unpaired electron of superoxide is donated to the quinone ring. This result has already been observed by us in related polyphenols scavenging superoxide [ 21 ]. The electron captured by the ring also has an effect on the C=O bond lengths as they become elongated by 0.03 Å.…”
Section: Resultssupporting
confidence: 84%
“…Our previous investigations on superoxide scavenging by embelin [ 31 ] emodin [ 32 ], and chalcones [ 33 ] described an additional mode of sequestering superoxide, through the π-π interaction between superoxide radical and the polyphenol. This scavenging mechanism is suggested for galangin as well, since, as described later in RRDE results, galangin is experimentally found to be an excellent scavenger of superoxide, and additional options need to be considered.…”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical technique [ 24 ] developed in our laboratory is very useful to study the scavenging of superoxide by small organic molecules found in fruit and vegetables. We have used it to describe the behavior of flavonoids [ 24 , 29 , 30 ], chalcones [ 31 ], coumarins [ 12 ], and quinones [ 32 , 33 , 34 ]. We also investigated the scavenging capacity of several integral natural products along with phytochemicals contained in the same natural products.…”
Section: Resultsmentioning
confidence: 99%